2016
DOI: 10.1093/rheumatology/kew324
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1 skews macrophage polarization and negatively influences phagocytosis of apoptotic cells

Abstract: Circulating monocytes from SLE patients display an M1-like phenotype compared with HCs, but in vitro differentiation abolishes this difference. HMGB1 skews differentiation of M2-like macrophages towards an M1-like phenotype and, subsequently, reduces phagocytosis of apoptotic cells. These data imply that the phenotype of monocytes or macrophages is determined by their environment, such as the presence of cytokines and HMGB1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 42 publications
2
48
0
3
Order By: Relevance
“…Recent work showed that HMGB1 modulates the polarization of macrophages ( Schaper et al, 2016 ; Son et al, 2016 ). The switch from a proinflammatory to a tissue-healing phenotype in macrophages is an essential step in muscle regeneration to limit the inflammatory response and favor myogenesis ( Arnold et al, 2007 ; Cohen and Mosser, 2013 ; Saclier et al, 2013 ; Wang et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work showed that HMGB1 modulates the polarization of macrophages ( Schaper et al, 2016 ; Son et al, 2016 ). The switch from a proinflammatory to a tissue-healing phenotype in macrophages is an essential step in muscle regeneration to limit the inflammatory response and favor myogenesis ( Arnold et al, 2007 ; Cohen and Mosser, 2013 ; Saclier et al, 2013 ; Wang et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Then we compared the phenotype of monocytes between SLE patients and healthy donors. Although the M1 and M2 phenotypes were designed to define macrophages, the specific markers were conclusively expressed on monocytes 32 . Our results showed lower expression of CD14 + CD163 + (M2-like) in SLE monocytes, which is consistent with previous research, however, the previous study reported no difference in the expression of CD86 between patients and healthy donors 32 , but we found extremely higher expression of CD86 in the patients’ monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the M1 and M2 phenotypes were designed to define macrophages, the specific markers were conclusively expressed on monocytes 32 . Our results showed lower expression of CD14 + CD163 + (M2-like) in SLE monocytes, which is consistent with previous research, however, the previous study reported no difference in the expression of CD86 between patients and healthy donors 32 , but we found extremely higher expression of CD86 in the patients’ monocytes. We supposed the reason might be the patient inclusion criteria, to avoid drug effect as much as possible, our patients were all diagnosed for the first time, only 5 of them had accepted prednisolone treatment before and the therapy duration was strictly controlled within 7 days, however, in their study, most of the patients had accepted prednisolone, hydroxychloroquine, or immunosuppressive therapy, the multiple drugs may affect the final phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies support dysfunctional and reduced phagocytosis in SLE patients, ultimately resulting in reduced clearance of apoptotic cells ( 56 58 ). Part of this phenotype may be regulated by UVB as HMGB1can skew macrophage polarization toward an M1-like phenotype diminishing their ability to phagocytose apoptotic cells ( 59 ).…”
Section: Introductionmentioning
confidence: 99%